Feasibility Analysis of Asian Redtail Catfish (Hemibagrus nemurus) Cultivation Floating Net Cage System in Pangkalan Kerinci Timur Village, Pangkalan Kerinci District, Pelalawan Regency, Riau Province - Addinul Akbar; Tince Sofyani; Zulkarnaini Zulkarnaini (Jurnal Perikanan dan Kelautan, 2023)
This research was conducted in Pangkalan Kerinci Timur Sub-district, Pangkalan Kerinci District, Pelalawan Regency, Riau Province to calculate the amount of investment, revenue, profit, and the feasibility level of Asian redtail catfish farming based on financial aspects using investment analysis, revenue, profit, revenue cost of ratio (RCR), financial rate of return (FRR), and payback period of capital (PPC). The method used in this research is the survey method while the determination of respondents is done by census. Data collection was carried out by direct observation, interview, and documentation with 10 mackerel fish farmers. The results showed that the cage size of Asian Redtail Catfish farmers consisted of size of 4×2×1.8 m³, the total investment was (IDR 22,048,997.00), the revenue received was (IDR 28,437,500.00/year), the profit received was (IDR8,442,629.00/year), RCR (1.42), FRR (38.29%), PPC (2.61). Meanwhile, for cages of size 4×4×1.8 m³, the total investment is (IDR30,027,500.00), the revenue received is (IDR 47,500,000.00/year), the profit received is (IDR19,066,669.00/year), RCR (1.67), FRR (63.49%), PPC (1.57). Based on the results of the RCR calculation of more than 1, FRR is greater than the bank interest rate of 6.4%, PPC is less than the maximum time required and the economic life of the equipment used for Asian redtail catfish farming is 3 years, then the Asian redtail catfish farming business is feasible to run but the income level of Asian redtail catfish floating net cage farmers is in the low category